Alpha interferon suppresses virion but not soluble human immunodeficiency virus antigen production in chronically infected T-lymphocytic cells. - Fernie, B F (1991)
Alpha interferon (IFN-alpha) is effective in preventing the release of human immunodeficiency virus (HIV) from chronically infected T-lymphocytic (ACH-2) and promonocytic (U1) cell lines stimulated with the phorbol ester phorbol-12-myristate-13 acetate (PMA). In the present study, we observed that together with particle production, shedding of HIV antigen (p24gag) occurs in the T-cell line ACH-2 both constitutively and after stimulation with PMA. IFN-alpha, although effective in suppressing the release of HIV particles, did not inhibit shedding of p24gag into the culture supernatants of either unstimulated or PMA-stimulated cells. These observations may be of relevance in the evaluation of the in vivo efficacy of IFN-alpha treatment of HIV-infected individuals as determined by levels of p24 antigen in plasma.